Effect of diffusion current on fill factor in organic solar cells. (18th April 2016) - Yu, Haomiao; Yi, Ruichen; Zhang, Jiawei; Yu, Anran; Peng, Huan; Qin, Jiajun; Hou, Xiaoyuan
Abstract: To identify the effect of drift/diffusion current on the fill factor (FF) of organic solar cells, the correlation between FF and drift/diffusion current is studied with thickness/type of donor material, temperature and doping as the experimental parameters. Experimental results show that FF is positively related to the diffusion current. Because of the suppression of carrier diffusion, generated carriers will accumulate at the donor–acceptor interface, resulting in carrier recombination.